“The Effectiveness of Integrating Spiritual Leadership and Skills Managerial in Improving Church Performance” - alvonco hutauruk, johnson (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study analyzes the effectiveness of integrating spiritual leadership and managerial skills in improving the performance of church organizations. Spiritual leadership integrates spiritual values with organizational goals, while managerial skills include the ability to plan, organize, execute, and control activities with a focus on efficiency and effectiveness in resource management. Using a literature review method and a descriptive qualitative approach, this study explores the principles of spiritual leadership rooted in Biblical values and modern management theories. The findings indicate that spiritual leadership, emphasizing role modeling, service, and a relationship with God, fosters harmony and intrinsic motivation within the organization. Meanwhile, managerial skills such as planning, organizing, executing, and controlling are essential for effective and efficient resource management. The study concludes that integrating spiritual leadership and managerial skills is key to creating an effective, ethical, and sustainable church amidst social, cultural, and economic changes.